2020
DOI: 10.1002/cam4.3321
|View full text |Cite
|
Sign up to set email alerts
|

Patient and caregiver benefit‐risk preferences for nonmetastatic castration‐resistant prostate cancer treatment

Abstract: Background Recently approved second‐generation androgen receptor inhibitors (SGARIs) for non‐metastatic castration‐resistant prostate cancer (nmCRPC) have similar efficacy but differ in safety profiles. We used a discrete choice experiment (DCE) to examine how nmCRPC patients and caregivers perceive the benefits versus risks of these new treatments. Methods An online DCE survey with 14 treatment choice questions was administered to nmCRPC patients and caregivers. Each choice question compared two hypothetical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 37 publications
2
36
0
Order By: Relevance
“…Even though survival is usually the most important treatment attribute for both patients and physicians, studies have demonstrated that other attributes such as adverse event profile or mode of administration (e.g., intravenous versus a one-off procedure) can play a significant role, with patients willing to make substantial trade-offs between survival and the risk of adverse events [7][8][9][10]. For this reason, the results from this MAIC demonstrate that TARE using SIR-Spheres can be a reliable treatment option when treatment attributes such as adverse event profiles, with the subsequent impact on QOL, are key to patients and physicians making therapeutic decisions [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though survival is usually the most important treatment attribute for both patients and physicians, studies have demonstrated that other attributes such as adverse event profile or mode of administration (e.g., intravenous versus a one-off procedure) can play a significant role, with patients willing to make substantial trade-offs between survival and the risk of adverse events [7][8][9][10]. For this reason, the results from this MAIC demonstrate that TARE using SIR-Spheres can be a reliable treatment option when treatment attributes such as adverse event profiles, with the subsequent impact on QOL, are key to patients and physicians making therapeutic decisions [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…This can improve patient experience, but also support optimum treatment selection for patients in an environment where there may be several treatment options available and more still in development. Interestingly, several patient preference studies in oncology have also demonstrated how important QOL is for patients with cancer, with some being willing to trade time alive for treatments with less negative impacts on their QOL [3][4][5][6][7][8][9][10]. Taking this into consideration a comparative analysis of time to deterioration (TTD) in QOL for different treatments for patients with advanced and unresectable hepatocellular carcinoma (HCC) would provide valuable information which can be used in treatment selection decisions.…”
Section: Introductionmentioning
confidence: 99%
“…Another study by Srinivas et al 18 reported that patients with nmCRPC and caregivers in the United States preferred treatments that lowered the risk of AEs such as fractures, falls followed by cognitive problems, fatigue, and rash. Additionally, both patients with nmCRPC and caregivers were willing to forego OS to reduce the risk of severity of the AEs.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, both patients with nmCRPC and caregivers were willing to forego OS to reduce the risk of severity of the AEs. 18 Another study on CRPC patient preference in Japan showed that the patients were more concerned about reduced quality of life (QoL) from the side effects of the treatment rather than extension of survival. 19 Our study found that although physicians were not willing to trade-off extension of time until cancer-related pain occurs with any single side effect because of treatment, they would do so with multiple lower risks of side effects because of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This was in accordance with a study that showed patients and caregivers are often more concerned with avoiding treatment-related risks rather than extending benefits. 20 Understanding patients’ expectations and good communication are necessary for effective clinical treatment decision-making.…”
Section: Discussionmentioning
confidence: 99%